Environmental ethics: principles and values for a responsible citizenship in global society - Lecaros Urzúa, Juan Alberto (Acta Bioethica, 2013)
Environmental ethics is an applied ethics which reflects about the grounds for duties and responsibilities of humans towards nature, living beings and future generations. The aim of this paper is to evaluate the planetary socio-ecological crisis guided by two axial ethical principles and an ethical-political concept derived: first, from the principle of responsibility and of care for the vulnerable being (current and future human beings and all other life on planet); second, the principle of ecological justice in its three complementary aspects: global justice (socio-economic inequalities at the global level); both justice intergenerational (future generations) and interspecies (principle of biospherical hospitality towards other living beings); and the ethical-political concept of ecological citizenship in a global society.